PENGARUH PENGGUNAAN ALAT MODIFIKASI TERHADAP KEMAMPUAN GERAK DASAR ATLETIK - Rizka Trisuci, Melinda; Budi, Budi (Journal of Physical Education and Sport Science, 2024)
Based on initial observations, in reality there are still people who are less interested in participating in learning basic athletic movements, because students prefer other games, one of which is football, especially male students. Every time learning basic athletic movements, students are less enthusiastic because students still want to play football. The purpose of this study was to determine the effect of using modified tools on basic athletic movement abilities at SD Negeri 3 Cisantana. The research method used in this research is the pre-experimental method. The research design used was a one group pretest-posttest design. The research sample was fourth grade students at SD Negeri 3 Cisantana, Cigugur District, Kuningan Regency. The data collection technique was in the form of an initial test before being given treatment and a final test after being given treatment. Data analysis techniques consist of normality test, hypothesis testing and N-Gain test. Based on the results of research and data processing and hypothesis testing, it can be concluded that there is an effect of using modified tools on basic athletic movement abilities at SD Negeri 3 Cisantana. The results of the N-Gain test showed that the increase in learning basic athletic movements through modified tools reached an average of 0.38 including the medium criteria.